Anxiolytic-like effects of Moringa oleifera in Swiss mice - Islam, Muhammad Torequl; Martins, Natália; Imran, Muhammad; Hameed, Aneela; Ali, Shinawar Waseem; Salehi, Bahare; Ahmad, Ishtiaque; Hussain, Ahmad; Sharifi-Rad, Javad (Cellular and Molecular Biology, 2020)
Moringa oleifera is evident to act against many neurological diseases, including muscle spasm, epilepsy, nervousness, fatigue, memory impairment, convulsion, and epilepsy. Anxiety represents the most common and disabling psychiatric condition, being often associated with depressive symptoms. This study investigated the anxiolytic-like effects of crude organic fractions of M. oleifera leaves in different behavioral paradigms that evaluate anxiety in mice. To this end, mice were administered with crude extracts (500 mg/kg, p.o.) and/or diazepam (2 mg/kg, p.o.), and submitted to behavioral tests. In the open-field test, the number of square field cross, grooming and rearing were calculated, while in light-dark and swing test were, respectively, the time spent in dark portion and number of swings. Each test was performed for 3 min. M. oleifera leaf methanol and n-hexane extracts elicited an anxiolytic-like effect observed by increased total time in the center and decreased number of rearings and groomings responses in the open field and swing tests, and residence in the dark portion in the light-dark box, similar to the diazepam group. A moderate anxiolytic effect was observed in the aqueous fraction group, while insignificant effects were recorded in the ethyl acetate fraction group in all test paradigms. In addition, both extracts potentiate the calming effects of diazepam in experimental animals. Preliminary phytochemical reports suggest that M. oleifera contains alkaloids, flavonoids, phenols, steroids, glycosides, saponins, tannin, terpenes, and gums. Of note, the results expand the understanding of M. oleifera effects in central nervous system and suggest that plant metabolites may be helpful for anxiety-related disorders management.